Analisis dan Perancangan Sistem Informasi Laboratorium Rumah Sakit Kanker Dharmais Dengan Menggunakan Total Architecture Syntesis - Ricky, Michael Yoseph (Bina Nusantara University, 2010)
The purposes of this research are to design and implementation of laboratory information systems (LIS) at the Laboratory of Cancer Hospital Dharmais (Dharmais Cancer Hospital). The methods used are the method of analysis, design methodology using Total Architecture Synthesis (TAS) and database design methods. Methods include analysis of the survey directly into the clinical laboratory Dharmais Cancer Hospital, and interviews with users who running the current system in Dharmais Cancer Hospital Clinical Laboratory. The design method using TAS. The results of this study is a single integrated Laboratory Information System applications with other systems that exist in Dharmais Cancer Hospital and also the delivery of feature inspection results by using text service and email, in addition to be taken directly to Dharmais Cancer Hospital and sent to the address. The conclusions from this study are all the transactions contained in Dharmais Cancer Hospital Clinical Laboratory have been computerized and integrated.